Avaliação da acessibilidade em escolas municipais de Lins, São Paulo - Médice, José (2008)
Architectural barriers are all the limitations that disabled or not disabled people face in their daily life and stop them from doing the basic right of any citizen to come and go. Objective: evaluate the architectural barriers related to constructions in municipal schools in Lins. Materials and Methods: A descriptive research was done in all the Municipal Schools in Lins. To collect the data it was used a checklist based in the ABNT 5090/04, where it was found elements referred to constructions and internal spaces. A comparison of the data collected in the schools with the measurements asked for the ABNT will be done to analyze the data. Results: It was noticed that: 1. the floors don´t have non-skid characteristics, alert and directional alert; 2. there are accented unevenness, with the predominance of steps with approximated measurements asked for the ABNT; 3. about the ramps, it was noticed that they have regular inclination and handrail with ramps and curves signaling, but they don´t have suitable markings and for this reason, the ABNT form was not obeyed; 4. the steps and the staircase have appropriate landings, but some of the staircases don´t have an appropriate handrail. Conclusion: The data of the present investigation provide a lot of important information to the leaders discuss about the accessibility and, who knows in the future, do something to realize the dream of having an educational system that could attend anyone with no distinction.